Optimization of sintering profiles for enhanced bonding of NanoCu particles - Lie, Joselyn (Nanyang Technological University, 2024)
To address the stringent demands of power electronics, such as increased current densities and higher operating temperatures, progressive innovations in packaging and assembly technologies are essential. The performance and reliability of these electronic systems rely heavily on the robustness of interconnect materials. Therefore, developing optimized bonding processes is important to sustain the device's functionality in extreme environments. The objective of this study is to develop optimized sintering conditions for bonding a copper die to both copper and silver direct bond copper (DBC) substrates using nano-copper (NC) paste. It has recently been found that NC paste exhibits outstanding electrical and thermal conductivity. Furthermore, it has good compatibility with copper-based components which are commonly used in the microelectronics industry. It is therefore being investigated as a cheaper substitute for nano-silver in electronic packaging applications. The goal is to determine the ideal temperature and process settings that optimize bond strength and reliability in these configurations. Thermogravimetric Analysis (TGA) was used to evaluate the thermal properties of the NC paste and assisted in identifying the suitable temperature range for the volatilization of organic components and capping layers within the paste. A multi-zone reflow oven was utilized to perform the sintering process, with temperature modifications made in stages 2 and 3 to optimize shear strength. To characterize the quality of the sintered joint, various characterization methods were utilized including destructive shear tests, Scanning Electron Microscope (SEM), and Electron Dispersive X-ray Spectroscopy (EDX). They are performed to study fracture morphology and material bonding. The average die shear strength of the NC joints increased with increasing sintering temperatures. The maximum shear strength reached 35.8 MPa for the copper die on copper substrate and 31.4 MPa for the copper die on silver DBC substrate, when stage 2 of the reflow oven was set to 250°C and stage 3 to 350°C. Three key observations were made in this study. First, higher temperatures in either stage 2, stage 3, or both generally resulted in higher shear strength. Second, lower shear strength was often associated with a higher carbon content, possibly due to incomplete removal of organic residues. Third, the effective adhesion area played a significant role in shear strength, as better contact between the die and substrate increased the bonding quality.